(untitled) (Research, Society and Development, 2020)
Teaching Science and Biology has demanded much more from the teacher than the mastery of content, because, even if this factor is important, the way they are being presented to students needs to be discussed. This research sought to understand the conceptions of science and biology teachers about the use of educational games in the school context. A qualitative approach of a descriptive nature was used, with the application of a questionnaire with two Biology teachers who teach in two schools in the state public school system of Alagoas, one in the city of Rio Largo and the other in the city of Maceió. Through textual discursive analysis, the results reveal the knowledge of teachers about the importance of using didactic games in science and biology teaching, but this rarely happens, which indicates the need to advance in discussions about the need to diversify teaching practice creating conditions for the construction of knowledge by different resources, among them, the didactic game.